Molecular mechanism of pH sensing and activation in GPR4 reveals proton-mediated GPCR signaling - Chongzhao You; Shimeng Guo; Tianwei Zhang; Xinheng He; Tianyu Gao; Wenwen Xin; Zining Zhu; Yujie Lu; Youwei Xu; Zhen Li; Yumu Zhang; Xi Cheng; et al. (Cell Discovery)
Abstract Maintaining pH homeostasis is critical for cellular function across all living organisms. Proton-sensing G protein-coupled receptors (GPCRs), particularly GPR4, play a pivotal role in cellular responses to pH changes. Yet, the molecular mechanisms underlying their proton sensing and activation remain incompletely understood. Here we present high-resolution cryo-electron microscopy structures of GPR4 in complex with G proteins under physiological and acidic pH conditions. Our structures reveal an intricate proton-sensing mechanism driven by a sophisticated histidine network in the receptor’s extracellular domain. Upon protonation of key histidines under acidic conditions, a remarkable conformational cascade is initiated, propagating from the extracellular region to the intracellular G protein-coupling interface. This dynamic process involves precise transmembrane helix rearrangements and conformational shifts of conserved motifs, mediated by strategically positioned water molecules. Notably, we discovered a bound bioactive lipid, lysophosphatidylcholine, which has positive allosteric effects on GPR4 activation. These findings provide a comprehensive framework for understanding proton sensing in GPCRs and the interplay between pH sensing and lipid regulation, offering insights into cellular pH homeostasis and potential therapies for pH-related disorders.